IMPLEMENTATION OF COLLAGE SKILLS ON EARLY CHILDHOOD CREATIVITY - Susiani, Tri Saptuti; Priyatnomo, Maulida Ajeng; Tantifah, Laras (Social, Humanities, and Educational Studies (SHES): Conference Series, 2018)
Creativity is one of the values in character education. But the fact is, according to Yohana (2013: 2) most children's artistic creativity is only extracted through drawing or coloring. Children will surely get bored if they only draw or color, therefore a breakthrough makes creativity through collage skills. The objectives of this study are: 1) Describe what collage skills are 2) Describe the creativity of early childhood; 3) Explain that collage skills can foster early childhood creativity. The method used is literature study which comes from books, literacy, notes, and reports that can be solved. The results of this study are; 1) Description of collage skills; 2) Description of the creativity of early childhood; 3) Collage skills can foster early childhood creativity. The conclusion of this study is that collage skills can foster early childhood creativity.